Die Designs of Cold Roll Forming Process for Car Bumper Using Advanced High Strength Steel. (2017) - Sheu, J.J.; Yu, C.H.; Wang, J.K.
Abstract: Cold roll forming (CRF) process can be adopted for making channels and tubes with complex cross section efficiently and integrate the welding and the heat treatment facilities to shorten production period. Advanced high strength steel is a hard-to-form material using the conventional forming method. Hot stamping process is a good way to reduce the forming load of the advanced high strength steel stamping. The heating and the cooling process is complex and difficult to control for the hot stamping method. Cold roll forming process is an alternative method to shape the advanced high strength steel using a series of rolls under the condition of room temperature. This paper proposed the CRF process and die designs for a car bumper structure with a cross section of two un-symmetric closed chambers using the advanced high strength steel with tensile strength of 1400 MPa. Designs of the roll flower, the forming rolls were evaluated using FEM method. The forming rolls were designed with relief and trap features to control the material locally and prevent the defects of folding and wrinkling. The simulation results showed the folding defect at the edge occurred during the closing step of the separated chambers due to the one side roll contact. Only the top roll touched the forming area of the upper blank without the support of the bottom roll due to the constraint of the chamber geometry. A fin pass design was adopted to make a proper preform of the top edge of the chambers. The simulation results showed the proposed design was able to prevent the folding defect and a sound product was obtained.